No effect of age on emotion recognition after accounting for cognitive factors and depression. Issue 11 (November 2019) - Murphy, Jennifer; Millgate, Edward; Geary, Hayley; Catmur, Caroline; Bird, Geoffrey
A decline in emotion recognition ability across the lifespan has been well documented. However, whether age predicts emotion recognition difficulties after accounting for potentially confounding factors which covary with age remains unclear. Although previous research suggested that age-related decline in emotion recognition ability may be partly a consequence of cognitive (fluid intelligence, processing speed) and affective (e.g., depression) factors, recent theories highlight a potential role for alexithymia (difficulty identifying and describing one's emotions) and interoception (perception of the body's internal state). This study therefore aimed to examine the recognition of anger and disgust across the adult lifespan in a group of 140 20–90-year-olds to see whether an effect of age would remain after controlling for a number of cognitive and affective factors potentially impacted by age. In addition, using an identity recognition control task, the study aimed to determine whether the factors accounting for the effects of age on emotion discrimination also contribute towards generalised face processing difficulties. Results revealed that discrimination of disgust and anger across the lifespan was predicted by processing speed and fluid intelligence, and negatively by depression. No effect of age was found after these factors were accounted for. Importantly, these effects were specific to emotion discrimination; only crystallised intelligence accounted for unique variance in identity discrimination. Contrary to expectations, although interoception and alexithymia were correlated with emotion discrimination abilities, these factors did not explain unique variance after accounting for other variables.